Pendekatan Psikologi Komunikasi Organisasi Pelajar Islam Indonesia (PII) Sumatera Selatan Pada Leadership Basic Training (LBT) - Muhammad Zepriansyah; Eni Murdiati; Muhammad Randicha Hamandia (CV. ITTC INDONESIA, 2023)
This research was conducted in South Sumatra, the city of Palembang, while the issues raised were (1) how to approach the organizational communication psychology of Indonesian Islamic Students (PII) South Sumatra in the 2018 Leadership Basic Training (LBT) (2) What are the inhibiting and supporting factors of the communication psychology approach Indonesian Islamic Student Organization (PII) South Sumatra in Leadership Basic Training (LBT) 2018. This study aims to find out how and what the psychological approach to communication for Indonesian Islamic Student Organizations (PII) is in Leadership Basic Training (LBT), then what are the factors factors that support and hinder the organizational communication psychology approach of Indonesian Islamic Students (PII) South Sumatra in Leadership Basic Training (LBT) This study used descriptive qualitative research, while the data collection techniques used during the research process were observation, interviews and literature study. The results of this study indicate that there are several psychological approaches such as using the Ta'dib system and having learning strategies in the form of several approaches, namely the process skills approach, the religious approach, and the group approach. As for the methods and learning techniques in Ta'dib which support the Leadership Basic Training (LBT), the selection of material is in accordance with the potential of the participants and instructors of Indonesian Islamic Students (PII), as well as in learning there are many methods used such as, Group dynmic, reflection interviews, informative dialogues, discussions, games, case studies and others. Participants who took part in the Leadership Basic Training (LBT) in 2018 totaled 40 (forty) participants who were successful in the communication psychology approach where the benchmark is until now active and has become a plenary cadre of cadres who have attended Leadership Advance Training (LAT) and have attended the Course There are 10 (ten) instructor education due to the inhibiting factor of the instructor team who do not understand the material or ta'dib system, guidelines and syllabus as a whole so that the targeted communication psychology approach is not delivered with the maximum further inhibiting factor, namely the lack of follow up from the instructor team to participants who have become cadres of Indonesian Islamic Students (PII)